Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This is the function: $$f(x)= \frac{x^3 + 3x^2+2x}{x^2-2x-8} $$ So I tried to find this limit: $$\lim_{x\to -2}\frac{x^3 + 3x^2+2x}{x^2-2x-8}=\left[\frac{-8-12-4}{4+4-8}=\frac{-24}{0}\right]= \lim_{x\to -2}\frac{x(x-1)(x-2)}{(x-4)(x+2)}$$ This isn't a case where numerator and denominator, after factorization, have some elements which can reduce a "problematic" element... I need to get rid of $(x+2)$ which makes the fraction explode but I don't know how.

share|cite|improve this question
$\color{red}+12$. And $x^3+3x^2+2x=x(x\color{red}+2)(x\color{red}+1)$. – David Mitra Feb 10 '13 at 0:05
What is that u doing in the denominator? Shouldnt that be a x? – CBenni Feb 10 '13 at 0:07
L'Hôpital's rule – Elements in Space Feb 10 '13 at 0:07
@CBenni editor displays 'x' but here it displays 'u'. – kr85 Feb 10 '13 at 0:10
If the numerator has finite, non-zero limit, and the denominator has a zero limit, then the limit is infinite or doesn't exist. For example $\lim\limits_{x\rightarrow1} {4\over (x-1)^2}=\infty$ and $\lim\limits_{x\rightarrow1} {4\over x-1 }$ does not exist (the limit from the right is $\infty$ and the limit from the left is $-\infty$). – David Mitra Feb 10 '13 at 0:28
up vote 6 down vote accepted

You have factor wrong your function, just do it in the following way $$\lim_{x\to -2}\frac{x^3 + 3x^2+2x}{x^2-2x-8} = \lim_{x \to -2} \frac{x(x+1)(x+2)}{(x-4)(x+2)} = \lim_{x \to -2} \frac{x(x+1)}{(x-4)} = \frac{-2(-2+1)}{-2-4} = -\frac{1}{3}$$

share|cite|improve this answer

I assume you meant $$f(x)=\frac{x^3+3x^2+2x}{x^2-2x-8}$$

Then $\lim_{x\to2-}f(x)$ is a indeterminate form or type $\frac{0}{0}$, therefore we apply l'Hopital rule and receive $$\lim_{x\to2-}f(x)=\lim_{x\to2-}\frac{3x^2+6x+2}{2x-2}=\frac{3\cdot4-2\cdot6+2}{-2\cdot2-2}=\frac{2}{-6}=-\frac{1}{3}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.